KEMITRAAN KOLABORATIF PEMERINTAH DAERAH SARBAGITA ( DENPASAR, BADUNG, GIANYAR, TABANAN) DENGAN PIHAK SWASTA PT NOEI DALAM PENGELOLAAN SAMPAH DI WILAYAH SARBAGITA - Patimah, Siti (CITIZEN CHARTER, 2014)
ABSTRACT Garbage issue is a difficult problem, it can not be solved easily. It needs a professional management to manage this problem well. However, every area has its own issue to build a technology for this professional management. The areas have minimum fund and lacks of human resources. That is why they do partnership to solve the trash issue. This is the reason why Sarbagita Government does partnership with PT. NOEI to manage the trash. In this partnership, there are some problems: until now, PT. NOEI have not managed the trash well and asked for tipping fee. It caused by an argument between both of them. Because of those issues, the purpose of this study is to know the partnership pattern between Sarbagita Government with PT.NOEI. This study used descriptive qualitative method to get the data; researcher observed by herself the phenomenon in the field and interviewed the people that have correlation with this partnership. Some conclusions were got in this study, the first PT. NOEI’s project plan was not ready yet, therefore PT.NOEI lacks of fund when it build a gasification technology. The second, there was unclear a contract letter. There wasn’t punishment if the second side did not do its responsibility well and also there was not a discussion of tipping fee there. The last, even there are some problems between Sarbagita Government and PT. NOEI, BPKS could do mediation by collaborative management to make this partnership runs well until now. Keywords: Public Private Partnership, Garbage Management, Sarbagita Government.